Polymyxin-resistant hypervirulent Klebsiella pneumoniae clinical isolates from a tertiary hospital in China: molecular mechanisms, antimicrobial susceptibility, and virulent phenotypes - Zhu, Xinyu; Yan, Jie; Lai, Xiyun; Zou, Tingjian; Chen, Mengyuan; Tang, Xiaofang; Wang, Qiang; He, Yuzhou (Frontiers in Microbiology, 2025)
BackgroundPolymyxins are critical last-resort treatments for infections caused by multidrug-resistant (MDR) gram-negative bacteria, especially carbapenem-resistant isolates. Recently, there has been a continuous increase in reports of polymyxin-resistant Klebsiella pneumoniae (PoRKP), which poses a major healthcare challenge. This study aims to investigate the current epidemiological trends and virulent phenotypes of PoRKP and to elucidate the mechanisms underlying polymyxin resistance.MethodsIn this study, 17 PoRKP strains were retrospectively identified from 2,146 Klebsiella pneumoniae (KP) clinical isolates collected in Hangzhou city from 2018 to 2021. We assessed the antimicrobial resistance and virulence profiles of 17 isolates, and they were subjected to molecular and genetic analyses and antimicrobial susceptibility testing.ResultsThe overall polymyxin resistance rate among the bacterial isolates included in this study was low (0.8%); however, all PoRKP isolates were MDR-positive. Notably, only three isolates carried mcr, whereas the vast majority either harbored mutations in mgrB (C28R or C28Y) or pmrA (T246A and R256G) leading to overexpression of the two-component systems, which we consider to be the primary mechanism underlying polymyxin resistance. Furthermore, five PoRKP isolates carrying hypervirulence genes exhibited a virulent phenotype in a Galleria mellonella infection model. Finally, recent antibiotic therapy, invasive procedures, and age were identified as important risk factors for the occurrence of polymyxin-resistant strains.ConclusionOur findings indicated a relatively low prevalence of plasmid-mediated mobile polymyxin resistance genes among PoRKP isolates, whereas the upregulation of the two-component systems (particularly phoPQ) played a more prominent role in mediating polymyxin resistance.